Pandemics and Travel : COVID-19 Impacts in the Tourism Industry - Seabra, Cláudia; Paiva, Odete; Silva, Carla (Writer on tourism); Abrantes, José Luís (Tourism security-safety and post conflict destinations., 2021)
Pandemics and Travel: COVID-19 Impacts in the Tourism Industryanalyses the wider impacts of epidemics, diseases and virus outbreaks on tourism and mobility. Chapters examine a wide range of issues, including the concept of Health Risk and Tourism and the impacts of the COVID-19 crisis.